Chaucer's Squire's Tale, Franklin's Tale, and Physician's Tale : An Annotated Bibliography, 1900-2005 - Bleeth, Kenneth, 1942- (Book collections on Project MUSE., 2017)
"Chaucer bibliographies series seeks to record all editions translations, and scholarship written in the twentieth and twenty-first centuries on particular tales. The present volume, the 9th in sequence, concerns the tales of the Physician, Squire and Franklin. The 1800 entries provide full bibliographic reference and brief description."--